Clinical leadership training in integrated primary care networks: a qualitative evaluation. Issue 1 (12th September 2022) - Nieuwboer, Minke; Van der Sande, Rob; Olde Rikkert, Marcel; Van der Marck, Marjolein; Perry, Marieke
Abstract : Objective: To explore how a clinical leadership training programme contributes to successful implementation of integrated dementia care in local primary care networks. Methods and analysis: A qualitative design was used in local primary care networks in the Netherlands. Twenty-six primary care professionals, nurses (n=22), general practitioners (n=2) and occupational therapists (n=2) followed a 2-year practice-based educational programme including individual coaching and interactive group training. Embedded leadership training created opportunities for direct application of acquired leadership skills. Reports of coaching sessions and transcripts of semi-structured interviews with 20 leadership trainees, 8 network members and a focus group interview with 9 leadership trainees were thematically analysed. Results: They identified 50 learning goals, mostly associated with personal leadership competences. These professionals perceived some improvement in their leadership behaviour and preferred a duo-network leadership arrangement. Individual coaching sessions and group training sessions were perceived as fruitful support. Coaching sessions were found to facilitate learning processes regarding personal competencies, collaboration issues and role clarification. Group meetings were appreciated for exercises on transformational leadership behaviour and exchange of experiences. Network leaders and members observed improved quality of care and mentioned continuity of leadership, perseverance of leaders and a sufficient time period to bring about change as important facilitating factors. Conclusion: Clinical leadership training to stimulate integrated primary care is promising as it was positively valued and contributed to improved perceived leadership competencies. Network leaders and members experienced improved quality of care when at least continuity in leadership was warranted.